Backmatter (Publication Ethics, Right Transfer Agreement for Publishing Form) - Istadi, Istadi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
Backmatter (Publication Ethics, Right Transfer Agreement for Publishing Form)